Adjuvant pioglitazone for unremitted depression: Clinical correlates of treatment response. Issue 3 (30th December 2015) - Lin, Kathleen Watson; Wroolie, Tonita E.; Robakis, Thalia; Rasgon, Natalie L.
Abstract: Previous studies suggest that insulin-sensitizing agents could play a significant role in the treatment of major depression, particularly depression in patients with documented insulin resistance or those who are resistant to standard psychopharmacological approaches. This study aimed to assess the effects on depressive symptoms with adjuvant treatment with the PPARγ-agonist pioglitazone. Patients ( N =37) with non-psychotic, non-remitting depression receiving standard psychiatric regimens for depression were randomized across an insulin sensitivity spectrum in a 12-week double blind, randomized controlled trial of pioglitazone or placebo. Improvement in depression was associated with improvement in glucose metabolism but only in patients with insulin resistance. An age effect was also shown in that response to pioglitazone was more beneficial in younger aged patients. Study findings suggest differential improvement in depression severity according to both glucose metabolic status and level of depression at baseline. A greater understanding of the reciprocal links between depression and IR may lead to a dramatic shift in the way in which depression is conceptualized and treated, with a greater focus on treating and/or preventing metabolic dysfunction. Highlights: This study assessed a PPARγ-agonist, pioglitazone, as an adjuvant treatment for depression. Subjects ( N =37) with received 90 days of pioglitazone in addition to treatment as usual. Improvement in depression associated with improvement in glucose metabolism in IR subjects. I Response to pioglitazone was stronger in younger patients.